[68Ga]-Dota Peptide PET/CT in Neuroendocrine Tumors: Main Clinical Applications - Giovannini, Elisabetta; Giovacchini, Giampiero; Borsò, Elisa; Lazzeri, Patrizia; Riondato, Mattia; Leoncini, Rossella; Duce, Valerio; Ciarmiello, Andrea (Current Radiopharmaceuticals, 2019)
Objective: Neuroendocrine Neoplasms (NENs) are generally defined as rare and heterogeneous tumors. The gastrointestinal system is the most frequent site of NENs localization, however they can be found in other anatomical regions, such as pancreas, lungs, ovaries, thyroid, pituitary, and adrenal glands. Neuroendocrine neoplasms have significant clinical manifestations depending on the production of active peptide. Methods: Imaging modalities play a fundamental role in initial diagnosis as well as in staging and treatment monitoring of NENs, in particular they vastly enhance the understanding of the physiopathology and diagnosis of NENs through the use of somatostatin analogue tracers labeled with appropriate radioisotopes. Additionally, the use of somatostatin analogues provides the ability to in-vivo measure the expression of somatostatin receptors on NEN cells, a process that might have important therapeutic implications. Results: A large body of evidences showed improved accuracy of molecular imaging based on PET/CT radiotracer with SST analogues (e.g. [68Ga]-DOTA peptide) for the detection of NEN lesions in comparison to morphological imaging modalities. So far, the role of imaging technologies in assessing treatment response is still under debate. Conclusion: This review offers the systems of classification and grading of NENs and summarizes the more useful recommendations based on data recently published for the management of patients with NENs, with special focus on the role of imaging modalities based on SST targeting with PET / CT radiotracers.
Keywords: lungs NENs